2008
DOI: 10.1007/s00256-008-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

A new tilt on pelvic radiographs: a pilot study

Abstract: As pelvic tilt increases, measurements used in protusio become unreliable, and computed tomography/magnetic resonance imaging are probably going to be more accurate as one can directly visualise pelvic intrusion. We recommend a lateral view to assess the degree of pelvic tilt in patients with protrusion to ensure these measurements are valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Several prior studies have reported on the difficulty and variability of predicting FAI based on AP radiographs [9,12,17,20,22] and this CT computational method might potentially reduce those errors. Using our methodology, it is possible not only to correct pelvic alignment, but also to simply define the acetabular rim.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several prior studies have reported on the difficulty and variability of predicting FAI based on AP radiographs [9,12,17,20,22] and this CT computational method might potentially reduce those errors. Using our methodology, it is possible not only to correct pelvic alignment, but also to simply define the acetabular rim.…”
Section: Discussionmentioning
confidence: 99%
“…A common radiographic finding related to focal acetabular overcoverage is referred to as the crossover sign (figure-of-eight) and exists when the lateral projection of the anterior wall crosses the posterior wall of the acetabular rim [11]. However, the degree of pelvic tilt and rotation changes the amount (or apparent existence) of crossover in patients, making it difficult to quantify on AP radiographs alone [9,12,17,20,22]. Moreover, the xray beam divergence in AP pelvis radiographs produces an overestimation of acetabular version by 4° [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should measure at least 1 mm in girls and at least 3 mm in boys [ 100 ]. CT or MRI can supply more accurate measurements [ 101 ].…”
Section: Imagingmentioning
confidence: 99%
“…hip dysplasia [10], [11]. To detect and quantify congenital or acquired hip dysplasia, especially when the treatment includes surgical intervention, the anterior and posterior acetabular sector angles (AASA and PASA, respectively), center-edge angle (CE), vertical-center-anterior angle (VCA) and acetabular index of depth to width (D/W) are usually evaluated [10,[12][13][14]. The angles serve to estimate alignment of the femoral head to the acetabulum, i.e.…”
Section: Introductionmentioning
confidence: 99%